Opuntia species: A comprehensive review of chemical composition and bio-pharmacological potential with contemporary applications - Chahdoura, Hassiba; Mzoughi, Zeineb; Ellouze, Ines; Generalić Mekinić, Ivana; Čmiková, Natália; El Bok, Safia; Majdoub, Hatem; Ben Hsouna, Anis; Ben Saad, Rania; Mnif, Wissem; Mosbah, Habib; Ben M'hadheb, Manel; et al. (South African journal of botany, 2024)
The aim of this review is to show the diverse applications and the phytochemical and pharmacological findings in connection with prickly pear plants of the Cactaceae family. Opuntia species, which are widely distributed in Africa, Asia, Australia and America and also play an important role in Mexico, have considerable health-promoting potential. Various parts of the plant, including cladodes, seeds, flowers, peels and fruits, contribute to its therapeutic efficacy. Opuntia is rich in phenolic antioxidants and pigments such as betalains and exhibits significant antimicrobial, antioxidant and anti-inflammatory properties. This review aims to provide scientific evidence for the chemical composition and beneficial properties of Opuntia sp. and to promote further research into their pharmacological and therapeutic effects. In addition, Opuntia sp. offer promising opportunities for various applications in both food and non-food sectors. [Display omitted] •Opuntia spp. (cladodes, fruits, flowers, seeds and peels) were studied.•Nutritional Value: Opuntia sp. are rich in essential nutrients such as vitamins, minerals, and antioxidants (polyphenols, flavonoids…) were found.•Health Benefits: Consumption of Opuntia sp. has been associated with various health benefits, including antioxidant and antimicrobial activity and reduced inflammation.•Opuntia spp. present a plethora of non-food and non-pharmaceutical applications, showcasing their versatility beyond culinary and medicinal realms (Animal Fodder, Natural Dye Production…).